Biomechanical analysis of lower limbs during stand-to-sit tasks in patients with early-stage knee osteoarthritis - Pan, Jing; Huang, Wenqin; Huang, Zhiguan; Luan, Jun; Zhang, Xiaohui; Liao, Bagen (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Knee osteoarthritis (KOA) is a common degenerative disease among the older people that severely affects their daily life. Previous studies have confirmed that movement biomechanics are altered in patients with KOA during task performance.However, changes that occur in lower limb joints and muscles in the three planes during stand-to-sit (STS) tasks in patients with early-stage KOA are unclear.Methods: A total of 36 participants were enrolled in this study, with 24 (8 males and 16 females) assigned to the KOA group and 12 (4 males and 8 females) to the control group. The Nexus Vicon motion capture system, along with Delsys wireless surface electromyography devices and two plantar pressure measurement mats, was used to record the test data. Visual 3D software was employed for data processing during STS tasks.Results: patients with KOA exhibited a greater ROM of pelvic joint, smaller ROM of hip and knee joints, and lower maximum angular velocity in the sagittal plane.Additionally, it demonstrated increased ROM of knee and ankle joints in the coronal plane. And they displayed lower vertical GRF on the affected side but higher integrated vGRF on both sides compared to the control group. Furthermore, patients with KOA exhibited higher PERM and PABM values in the lower limb joints, as well as smaller knee PADM and ankle PEM values. Maximum activation levels of the GMed, affected-side's GM, ST, RF, and TA muscles were lower in patients with KOA compared to controls. Conversely, the activation level of the BF muscle was higher.Moreover, the integral EMG values of GMed, GM, ST, VL, RF, VM, and TA muscles on the affected side were lower, except for the BF muscle.Conclusion: Patients with early-stage KOA exhibited consistent changes in sEMG parameters and biomechanical alterations in the sagittal plane, as observed in previous studies. However, differences in parameters were observed in the coronal and horizontal planes in this study. The noninvasive analysis of 3D parameters related to the altered motion patterns may facilitate early detection of KOA.